Globalization and State Capacity: The Philippines - Epictetus Patalinghug (Philippine Institute for Development Studies (PIDS), 2003)
The arrival of globalization has brought about a lot of challenges for nations to meet. This paper takes a look at the capability of the Philippine state to cope with the demands of globalization. It documents the rules, laws, regulations, institutions and agencies that underlie the administrative capacity of the Philippines to promote trade and investments, and thereby achieve economic growth. A review and analysis of Philippine practices and experience is undertaken to determine the states readiness for globalization. The study will cover three aspects of state capacity that contribute to the promotion of trade and investments: (1) administrative capacity, (2) systems of transparency and accountability, and (3) legal and judicial frameworks. Finally the paper recommends areas wherein the Philippine government must focus on based on the three aspects as well as suggests follow up in-depth studies on issues covering: capacity to promote healthy competition; regulatory framework and capacity; capacity to develop industries, sectors and regions; policies for social development, redistributive justice, and poverty reduction; policies to promote performance, productivity, and competitiveness; and policies to protect the environment.
Keywords: 330; globalization; transparency; economic development; Globalisierung; Institutionelle Infrastruktur; Bürokratie; Philippinen